PERANCANGAN HOTEL BISNIS DI KABUPATEN SINTANG - Fathurrahman, Muhammad Ardi; Irwin, Irwin; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2021)
Business hotels are hotels that are intended for people who live for a short period of time and these hotels are usually located in the center of the city crowd, guests who come mostly for business, meetings, seminars, trade and official company events. With the development of an area, the local community and immigrants will also increase in number, such as in Sintang district which will become the capital of the blooming province of West Kalimantan to become a new province, namely the province of Kapuas Raya, which can be sure to be the center of the crowd so that it really needs a place to live for a while, such as hotels, especially business hotels, to accommodate activities aimed at doing business, so that the economy in the area is maintained. In designing this hotel, it uses a method starting from the analysis of the design function, which will be divided into four functions, namely the management function, business function, recreation function and residential function. The design of this business hotel will also introduce existing cultures in Sintang district, one of which is handicraft woven handicrafts from the Dayak tribe in Sintang district, which motivation will be applied to certain parts of the building, such as secondary skin, ceiling patterns and part of the room walls. aims to introduce one of the handcrafts of the Dayak tribe in Sintang district.